Reimagining student employability: a case study of policy and practice transformation. Issue 5 (3rd September 2019) - Campbell, Matthew; Cooper, Berni; Rueckert, Caroline; Smith, Judith
ABSTRACT: Within Australian higher education, there has been an evolving of employability policy, realised in curriculum, at an intersection of the constructs of employment, work-readiness, life-long learning, and career development. The enactment of employability policy has driven an evolution in the practices of higher education in both curriculum and student support. This paper presents a case study of an Australian university which has reimagined the delivery of career and student support services through a framework that envisions preparing students for future worlds of work. The emergent policy framework has transformed organisational structures, human resources, and connections between student support practices and curriculum design. This transformation has generated new intersections of practice and is challenging institutional constructs of expertise. This case study provides transferrable learnings for broader considerations of higher education policy and practice as employability becomes the core driver of student success, and explores layered discourses of policymaking across an institution.